The Roles of Political Network Diversity and Social Media News Access in Political Participation in the United States and South Korea - Sun Kyong Lee; Kyun Soo Kim; Amanda Franklyn (Asian Journal for Public Opinion Research)
Two surveys for exploring communicative paths toward political participation were conducted with relatively large samples of Americans (*N* = 1001) and South Koreans (*N* = 1166). Hierarchical regression modeling of the relationships among demographics, personal networks, news consumption, and cross-cutting discussion and political participation demonstrated mostly commonalities between the two samples, including the interaction between political diversity and Twitter usage for news access but with distinct effect sizes of cross-cutting discussion on political participation. We attribute the differences to the two countries' distinct histories of democracy and culture, and the commonalities to the general relationships between cross-cutting discussion and political participation moderated by strong ties political homogeneity.